Action research and participatory democracy in social enterprise. Issue 1 (8th October 2019) - Gleerup, Janne; Hulgaard, Lars; Teasdale, Simon
Abstract : Purpose: The purpose of this paper is to introduce the reader to the Nordic tradition of Critical Utopian Action Research (CUAR) and to demonstrate how CUAR might reinvigorate participatory democracy as an intrinsic characteristic of social enterprise. This leads us to sketch out the beginnings of how researchers might work with communities to help realise their democratic impulses through social enterprise. Design/methodology/approach: This paper aims to synthesise the participatory action research literature, particularly CUAR, with literature on social enterprise and democracy to demonstrate how the two approaches might fruitfully be combined. Findings: The authors show how CUAR might be utilised by researchers, to articulate new social enterprise organisational responses to local problems or to reinvigorate democracy within existing social enterprises. Originality/value: This exploratory paper marks (we believe) the first attempt to bring together social enterprise and CUAR.